1996
DOI: 10.1136/pgmj.72.848.349
|View full text |Cite
|
Sign up to set email alerts
|

Changes in haemodynamic parameters following Tai Chi Chuan and aerobic exercise in patients recovering from acute myocardial infarction

Abstract: SummaryIn this study, 126 patients (90 males, average age 56 years, range 39-80) were randomised to Wu Chian-Ch'uan style Tai Chi (38), aerobic exercise (41) or a non-exercise support group (47) following acute myocardial infarction. Patients attended twice weekly for three weeks then weekly for a further five weeks. Heart rate and blood pressure were recorded before and after each session. Over the 11 sessions of exercise there was a negative trend in diastolic blood pressure only in the Tai Chi group (Rs=0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
3
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 8 publications
0
107
3
3
Order By: Relevance
“…Scientific evaluation of Tai Chi on lipid profiles has been going on for decades. Channer et al (1996) revealed that Tai Chi was related to better long-term blood pressure control than aerobic exercise in post-myocardial infarction patients. It was postulated that Tai Chi played a primary or complementary role in primary and secondary prevention in cardiovascular disease, and that improving lipid profiles could be one of the mechanisms (La Forge, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Scientific evaluation of Tai Chi on lipid profiles has been going on for decades. Channer et al (1996) revealed that Tai Chi was related to better long-term blood pressure control than aerobic exercise in post-myocardial infarction patients. It was postulated that Tai Chi played a primary or complementary role in primary and secondary prevention in cardiovascular disease, and that improving lipid profiles could be one of the mechanisms (La Forge, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in blood pressure have also been shown in patients recovering from acute myocardial infarction [41]. In this three-armed randomised controlled study (n=126), blood pressure fell in the Tai Chi and aerobic exercise groups, but a true comparator group was not available due to low rates of study completion in the non-exercise support group (8%) and thus there was risk of placebo effect.…”
Section: Blood Pressure and Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Despite improvements in research designs, well-controlled trials assessing the effect of Tai Chi on cardiovascular risk factors are lacking [39,41].…”
mentioning
confidence: 99%
“…Recent studies also prove that TC is safe and effective for patients with myocardial infarction, bypass surgery and heart failure. Channer et al 45 reported that the application of TCC for patients with acute myocardial infarction was safe and showed benefits to blood pressure. There are several reasons to recommend TCC as an exercise program for patients with CABG.…”
Section: Tai Chi Chuan Trainingmentioning
confidence: 99%